IDENTIFIKASI FAKTOR RISIKO KECELAKAAN DI PERLINTASAN SEBIDANG : KAJIAN PADA DAERAH OPERASI 1 - Putri Diasmara, Amanda
The high number of road user accidents at level crossings is one of the serious problems faced by PT KAI, especially Operation Area 1. The current warning system consisting of active and passive systems has not been able to support the behavioural aspects of road users in making decisions. Therefore, the safety of road users needs to be evaluated through an assessment of the factors that affect the rate of non-compliance. One of the research methods that can be used to evaluate the safety of road users is to collect field data in the form of assessing crossing characteristics, calculating vehicle volume, calculating total warning system duration, and calculating several non-compliance. In addition, the assessment of road users motivation in decision-making is carried out through interviews. By having quantitative data from the results of field data collection along with the results of interviews, it can be seen the factors that most influence the behavior of road users. The results of this study indicate that the level of frustration is the main factor causing non-compliance with road users. The level of frustration is caused by the reluctance to wait for the warning system, the level of congestion, and pressure from other road users to speed up. The current warning system which still provides an opportunity for road users to break through and the absence of strict enforcement of sanctions is also a supporting factor for the warning system that should be improved. The results show that improving the quality of the active warning system such as adding a boom gate is an example of applicable risk mitigation. This solution can be continued by coordinating with the local government to strictly enforce regulations for violators of the warning system. With the quality of an adequate active warning system and strict law enforcement, it is expected to reduce the number of non-compliance at level crossings.